Pembuatan Biodiesel Dari Minyak Nyamplung (Calophyllum Inophyllum) Menggunakan Katalis Geopolimer: Pengaruh Temperatur Dan Rasio Mol Minyak:Metanol - Mohd Fajri Amrullah; Edy Saputra; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biodiesel is an alternative energy to replace fossil fuels. It can be made by transesterification process of vegetable oils. Process of making biodiesel commonly use NaOH or KOH as homogeneous catalyst which has the disadvantage the formation of by products such as soaps and the complexity of the separation of catalyst. Therefore, in this study biodiesel was synthesized from calophyllum inophyllum oil by using geopolymer catalyst. Geopolymer was synthesized by mixing sodium silicate, metakaolin, NaOH, and water. Several variations of the process variables were done to assess its influence on yield of biodiesel. The variables were used consist of a dependent variables and independent variables. The dependent variables were calophyllum inophyllum oil weight of 50 grams, 3%-wt of catalyst concentration, reaction time of 120 minutes, and stirring speed of 400 rpm, while the independent variables which variation molar ratio of oil:methanol 1:3, 1:6, 1:9, 1:12 and variations of temperature 55, 60, 65 oC. Physical characterization were done including density 873 kg/m3, kinematic viscosity 4.46 mm2/s, acid number 0.49 mg-KOH/g biodiesel and flash point 140°C respectively accordance with the standards of Indonesian biodiesel (SNI 7182:2015).Keywords: biodiesel, catalyst, calophyllum inophyllum oil, geopolymer, yield